Optimization of Queries on Databases by Using the Ingres Algorithm - Nudin, Nur lhsan; Sifaunajah, Agus; Arifin, Muhyiddin Zainul (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Bahrul Ulum Islamic Boarding School is the oldest cottage in Jombang district which was founded in 1830 AD until now. which of course has a very large number of students, both students and alumni status. The author wishes to research how to manage data in information systems with hundreds or millions of data quickly and easily. Proper query design is very influential on information system applications, if you only rely on conventional query techniques, the results needed to process queries are relatively slow, and the time required is also longer. The purpose of this research is to optimize the query using the ingress algorithm which will later be tested and compared the results with queries that have not been optimized or conventional to determine the extent to which the query process can be accelerated. The experimental results show that the execution time is more effective and faster using an optimized command using the Ingres algorithm with an average processing time of 0.13226 seconds, and an average request that has not been optimized 0.2079 seconds, in other words the result is 65% faster than unoptimized queries.